Characterization of Growth and Reproduction Performance, Transgene Integration, Expression, and Transmission Patterns in Transgenic Pigs Produced by piggyBac Transposition-Mediated Gene Transfer. Issue 4 (1st October 2016) - Zeng, Fang; Li, Zicong; Cai, Gengyuan; Gao, Wenchao; Jiang, Gelong; Liu, Dewu; Urschitz, Johann; Moisyadi, Stefan; Wu, Zhenfang
ABSTRACT: Previously we successfully produced a group of EGFP-expressing founder transgenic pigs by a newly developed efficient and simple pig transgenesis method based on cytoplasmic injection of piggyBac plasmids. In this study, we investigated the growth and reproduction performance and characterized the transgene insertion, transmission, and expression patterns in transgenic pigs generated by piggyBac transposition. Results showed that transgene has no injurious effect on the growth and reproduction of transgenic pigs. Multiple copies of monogenic EGFP transgene were inserted at noncoding sequences of host genome, and passed from founder transgenic pigs to their transgenic offspring in segregation or linkage manner. The EGFP transgene was ubiquitously expressed in transgenic pigs, and its expression intensity was associated with transgene copy number but not related to its promoter DNA methylation level. To the best of our knowledge, this is first study that fully described the growth and reproduction performance, transgene insertion, expression, and transmission profiles in transgenic pigs produced by piggyBac system. It not only demonstrates that piggyBac transposition-mediated gene transfer is an effective and favorable approach for pig transgenesis, but also provides scientific information for understanding the transgene insertion, expression and transmission patterns in transgenic animals produced by piggyBac transposition.